2018
DOI: 10.1016/j.jcrc.2018.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Development and feasibility of a smartphone-based test for the objective detection and monitoring of attention impairments in delirium in the ICU

Abstract: DelApp-ICU shows promise for assessing inattention and delirium in ICU patients, including longitudinally monitoring deficits and providing a metric of delirium severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The DelApp is a computerized, objective test of arousal and attention that is implemented on a smartphone and is for use in both the general population and ICU patients. Case-control studies show a high sensitivity and a moderate-to-high specificity of DelApp in the detection of delirium 235,236 .…”
Section: Delirium Assessment In the Icumentioning
confidence: 99%
“…The DelApp is a computerized, objective test of arousal and attention that is implemented on a smartphone and is for use in both the general population and ICU patients. Case-control studies show a high sensitivity and a moderate-to-high specificity of DelApp in the detection of delirium 235,236 .…”
Section: Delirium Assessment In the Icumentioning
confidence: 99%
“…Only 10 papers were low risk in blinding of outcome measures, 5,20,44,46,48,51,55,66,67,70 with most papers presenting unclear risk due to a lack of clarity around blinding details. In terms of incomplete outcome data, 12 papers had high risk due to an absence of a published protocol 5,29,30,43,45,46,48,55,61,65,67,68 . The highest RoB was found regarding confounding variables; only five papers 29,39,45,54,57,61 had low RoB in confounding variables, with the remaining papers presenting a high risk.…”
Section: Resultsmentioning
confidence: 99%
“…Only four assessments used were delirium‐specific: the DRS‐R98, 18 the Cognitive Test for Delirium (CTD), 28 The Edinburgh Delirium Test Box (EDTB) 29 and the DelApp, 30 with less than half of the included studies (14 studies) using these tools. Included studies using the DRS‐R98 reported results for its constituent 13 symptom domains for example, hallucinations, delusions, motor agitation, etc., in addition to the overall DRS‐R98 score.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies are needed to evaluate the utility of OSLA in different populations (eg, palliative care, emergency departments) and to assess the prognostic value of higher OSLA scores for unfavourable outcomes in prospective cohort studies. A recent study provided preliminary support for the utility of the OSLA as a tool for detailed measurement of level of arousal in ICU patients, 27 though the OSLA itself has yet to be formally validated in this population.…”
Section: Discussionmentioning
confidence: 99%